Self-Assessment of Oral Health Status among Adults Residing at Chautara, Sindhupalchowk, Nepal - Dahal, Sirjana; Khapung, Anju; Dahal, Samarika; Poudel, Prakash (Journal of Nepal Health Research Council, 2025)
Background: Little is known about attitudes and practices regarding oral health of developing countries. This study aimed to determine the self-assessment of oral health status among adults residing at Chautara, Sindhupalchowk, Nepal.Methods: A descriptive cross-sectional study was conducted among 440 adults selected by convenience sampling method. Interview using WHO oral health questionnaire for adults 2013 was taken after receiving informed consent. Data were entered in Microsoft Excel Sheet and analysed in SPSS version 24. Mean, standard deviation, frequency and percentage were calculated.Results: Majority had positive assessment regarding their teeth (366, 83.18%) and gums (384, 87.27%). Many (417, 94.77%) cleaned their teeth ≥one times a day. Majority used toothbrush (434, 98.64%) and paste (411, 93.41%) for cleaning their teeth. Some, (184, 41.82%) visited a dentist at least once in their lifetime and the main reason was pain or trouble in teeth/gums/mouth (94, 51.09%). Very often, they faced problems chewing (31, 7.0%) and biting (27, 6.1%) foods. They mostly consumed tea with sugar (132, 30.0%) and biscuits, cakes and cream cakes (59, 13.4%) several times a day. Most of them smoked cigarettes every day (93, 21.1%), followed by tobacco chewing (67, 15.2%). In the past 30 days, 179 (40.7%) drank one or more drinks of alcohol.Conclusions: The study findings showed that most of the adult residents of Chautara, had positive self-assessment of their oral health status. However, they faced many oral health problems which may be due to their unhealthy lifestyle suggesting need for oral health awareness programs.Keywords: Adults; oral health; self-assessment.